A comparison of weekly versus 3-weekly cisplatin during adjuvant radiotherapy for high-risk head and neck cancer. (August 2016) - Oosting, Sjoukje F.; Chen, Tom W.W.; Huang, Shao H.; Wang, Lisa; Waldron, John; Gilbert, Ralph; Goldstein, David; Halmos, Gyorgy B.; Witjes, Max J.H.; Gietema, Jourik A.; O'Sullivan, Brian; Langendijk, Johannes A.; et al.
Graphical abstract: Highlights: Half of high-risk HNSCC patients are not eligible for addition of cisplatin to RT. Weekly 50 mg/m 2 cisplatin results in a higher cumulative dose than 3-weekly 100 mg/m 2 . Efficacy of weekly 50 mg/m 2 cisplatin remains to be evaluated. Summary: Objectives: To compare cumulative cisplatin dose and toxicity between patients who received 3-weekly versus weekly cisplatin during adjuvant radiotherapy for high-risk head and neck squamous cell carcinoma (HNSCC). Materials and methods: Consecutive HNSCC patients with involved resection margins and/or extra-capsular extension in two tertiary cancer centers with different institutional practices were identified. Cumulative cisplatin dose was calculated and information on toxicity reviewed and compared between patients who received 3-weekly versus weekly cisplatin. Results: Of 270 high risk patients, 60 received 3-weekly 100 mg/m 2 and 48 received weekly 50 mg/m 2 cisplatin during adjuvant radiotherapy (60–66 Gy in 30–33 fractions). Fourteen patients received other chemotherapy schedules and 148 received no chemotherapy. Mean cumulative cisplatin dose was 199.4 mg/m 2 (standard error (SE) 5.4) in 3-weekly versus 239.8 mg/m 2 (SE 11.0, P = 0.001) in weekly treated patients. Cumulative cisplatin ⩾200 mg/m 2 was given to 67.7% of patients in the 3-weekly cohort and 85.2% ( P = 0.039) in the weekly cohort. The rate of feeding tube dependency 6 months after treatment, osteoradionecrosis, neutropenic fever, and persistent renal function decline were not statistically different. Conclusions: About one half of high-risk HNSCC patients are not eligible for cisplatin during postoperative radiotherapy. Patients treated with weekly 50 mg/m 2 cisplatin received a higher cumulative dose with comparable toxicity as patients who received 3-weekly 100 mg/m 2 cisplatin. Efficacy and applicability to the frequently used weekly 40 mg/m 2 schedule remains to be evaluated.